Mutations in Drosophila heat shock cognate 4 are enhancers of Polycomb. - Mollaaghababa, R.; Sipos, L.; Tiong, S.Y.K.; Papoulas, O.; Armstrong, J.A.; Tamkun, J.W.; Bender, W. (Proceedings of the National Academy of Sciences of the United States of America, 2001)
The homeotic genes controlling segment identity in Drosophila are repressed by the Polycomb group of genes (PcG) and are activated by genes of the trithorax group (trxG). An F(1) screen for dominant enhancers of Polycomb yielded a point mutation in the heat shock cognate gene, hsc4, along with mutations corresponding to several known PcG loci. The new mutation is a more potent enhancer of Polycomb phenotypes than an apparent null allele of hsc4 is, although even the null allele occasionally displays homeotic phenotypes associated with the PcG. Previous biochemical results had suggested that HSC4 might interact with BRAHMA, a trxG member. Further analyses now show that there is no physical or genetic interaction between HSC4 and the Brahma complex. HSC4 might be needed for the proper folding of a component of the Polycomb repression complex, or it may be a functional member of that complex.